1985
DOI: 10.1073/pnas.82.19.6522
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequences of the Pseudomonas savastanoi indoleacetic acid genes show homology with Agrobacterium tumefaciens T-DNA

Abstract: We report the nucleotide sequences of iaaM and iaaH, the genetic determinants for, respectively, tryptophan 2-monooxygenase and indoleacetamide hydrolase, the enzymes that catalyze the conversion of L-tryptophan to indoleacetic acid in the tumor-forming bacterium Pseudomonas syringae pv. savastanoi. The sequence analysis indicates that the iaaM locus contains an open reading frame encoding 557 amino acids that would comprise a protein with a molecular weight of 61,783; the iaaH locus contains an open reading f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(106 citation statements)
references
References 34 publications
1
103
0
2
Order By: Relevance
“…This is an especially interesting possibility considering that the iaaH and iaaM genes of Pseudomonas syringae pv. savastanoi, which code for the synthesis of indol-3-acetic acid by this bacterium, are related at the nucleotide sequence level to those encoded on the T region of octopine-and nopaline-type Ti plasmids (52). That the Ti plasmid may be transmissible to P. syringae pv.…”
Section: Resultsmentioning
confidence: 99%
“…This is an especially interesting possibility considering that the iaaH and iaaM genes of Pseudomonas syringae pv. savastanoi, which code for the synthesis of indol-3-acetic acid by this bacterium, are related at the nucleotide sequence level to those encoded on the T region of octopine-and nopaline-type Ti plasmids (52). That the Ti plasmid may be transmissible to P. syringae pv.…”
Section: Resultsmentioning
confidence: 99%
“…One of the roles suggested for production of IAA by fungus is to mediate fungal-plant interaction. A high concentration of IAA inhibited the hypersensitive response (Robinette and Matthysse, 1990;Jouanneau et al, 1991) and suppressed the expression of plant defense genes (Yamada et al, 1985;Shinshi et al, 1987). The present study focuses on production and characterization of IAA produced by the isolate T. viride VKF3.…”
Section: Issn: 2319-7706 Volume 6 Number 11 (2017) Pp 2692-2701mentioning
confidence: 99%
“…1, the corresponding amino acid sequences of the encoded polypeptides, AtAMIX to AiAMI4, are compared with the prokaryotic sequences and particularly to that of Rhodococcus sp. amidohydrolase (EC 3.5.1.4, GenBank M74531), an enzyme known to hydrolyze IAM into IAA and ammonia (Klee et al, 1984;Yamada et al, 1985), but utilizing also, e.g., fatty acid amides (Cravatt et al, 1996) as substrates. The active site of this enzyme has been analyzed in most detail (Kobayashi et al, 1997) and was shown to include Asp-168 and Ser-173 rather than Cys-181, a residue hitherto assumed to be involved in catalysis (Fig.…”
Section: Molecular Cloning Of Arabidopsis Amidase 1 Cdna and Its Funcmentioning
confidence: 99%